Performance analysis of the closed loop supply chain - Farazee MA Asif; Carmine Bianchi; Amir Rashid; Cornel Mihai Nicolescu (Journal of Remanufacturing, 2012)
Purpose: The question of resource scarcity and emerging pressure of environmental legislations has brought a new challenge for the manufacturing industry. On the one hand, there is a huge population that demands a large quantity of commodities; on the other hand, these demands have to be met by minimum resources and pollution. Resource conservative manufacturing (ResCoM) is a proposed holistic concept to manage these challenges. The successful implementation of this concept requires cross functional collaboration among relevant fields, and among them, closed loop supply chain is an essential domain. The paper aims to highlight some misconceptions concerning the closed loop supply chain, to discuss different challenges, and in addition, to show how the proposed concept deals with those challenges through analysis of key performance indicators (KPI). Methods: The work presented in this paper is mainly based on the literature review. The analysis of performance of the closed loop supply chain is done using system dynamics, and the Stella software has been used to do the simulation. Findings: The results of the simulation depict that in ResCoM; the performance of the closed loop supply chain is much enhanced in terms of supply, demand, and other uncertainties involved. The results may particularly be interesting for industries involved in remanufacturing, researchers in the field of closed loop supply chain, and other relevant areas. Originality: The paper presented a novel research concept called ResCoM which is supported by system dynamics models of the closed loop supply chain to demonstrate the behavior of KPI in the closed loop supply chain.
Keywords: 650; closed loop supply chain; key performance indicator; logistics; operations management; production management; performance measurement; resource conservative manufacturing; supply chain management; system dynamics; remanufacturing; Lieferkette; Betriebliche Kennzahl; Logistik; Produktionswirtschaft; Performance-Messung; Umweltmanagement; System Dynamics; Produkt-Recycling